Set up the composite result function.
f
(
g
(
x
)
)
Evaluate
f
(
g
(
x
)
)
by substituting in the value of
g
into
f
.
4
(
x
−
2
)
Apply the distributive property.
f
(
x
−
2
)
=
4
x
+
4
⋅
−
2
Multiply
4
by
−
2
.
f
(
x
−
2
)
=
4
x -8
Step-by-step explanation:
Answer:
Step-by-step explanation:
Given a curve defined by the function 2x²+3y²−4xy=36
The total differential of this function with respect to a variable x makes the function an implicit function because it contains two variables.
Differentiating both sides of the equation with respect to x we have:
4x+6ydy/dx-(4xd(y)/dx+{d(4x)/dx(y))} = 0
4x + 6ydy/dx -(4xdy/dx +4y) = 0
4x + 6ydy/dx - 4xdy/dx -4y = 0
Collecting like terms
4x-4y+6ydy/dx - 4xdy/dx = 0
4x-4y+(6y-4x)dy/dx = 0
4x-4y = -(6y-4x)dy/dx
4y-4x = (6y-4x)dy/dx
dy/dx = (4y-4x)/6y-4x
dy/dx = 2(2y-2x)/2(3y-2x)
dy/dx = 2y-2x/3y-2x proved!
Answer:1/16
Step-by-step explanation:1/4= .25
Divide .25 by 4( for the four students) = .0625
.0625 is equivalent to 1/16
Answer:
1 : 1
Step-by-step explanation:
When a circle is inscribed in a cylinder, the height of the cylinder is equal to the diameter of the sphere and the radius of the cylinder is same as that of the sphere.
Let the radius of sphere is r.
height of cylinder, h = 2r
radius of cylinder = r
Surface area of sphere, A = 4πr²
lateral surface area of cylinder, A' = 2 πrh
A' = 2πr x 2r = 4πr²
The ratio of surface area of sphere to the lateral surface area of cylinder is 1 : 1.